Dinamika Agroforestry Tegalan di Perbukitan Menoreh, Kulon Progo, Daerah Istimewa Yogyakarta (Jurnal Penelitian Kehutanan Wallacea, 2014)
Land management in agroforestry systems requires species selection and proper silviculture. Selection of species and silvicultural treatments aimed at maintaining competition in obtaining a light, water and nutrients. Farmers choose the species based on the economical factor. This study aims to determine the composition of plant species in dry land agroforestry in Menoreh Hill, Kulon Progo District. Research done by survey method. Plot observation was divided into three level of light intensity: : a) early agroforestry (light intensity >50%), b) middle agroforestry, (light intensity 30-50%), c) further agroforestry (light intensity
Keywords: Composition of plant species; dry land agroforestry; Menoreh Hill